Edukasi oleh KPPS dalam Penyelengaraan PEMILU Tahun 2024 Di Dusun Kantan Desa Sendoyan - Rosa (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2025)
General Elections (PEMILU) constitute one of the most important moments in Indonesia’s democratic system. In the context of the 2024 General Election in Dusun Kantan, Sendoyan Village, the role of the Voting Organizing Group (KPPS) has a significant impact on ensuring an effective and transparent electoral process. This study aims to examine how the educational efforts provided by KPPS influence the community, particularly in increasing public participation, improving the quality of election administration, and encouraging citizens to exercise their voting rights responsibly. This research employs a qualitative approach with a descriptive research design. The data sources consist of the head and members of KPPS in Dusun Kantan. Data collection techniques include observation, interviews, and documentation. Data analysis is conducted using qualitative data analysis techniques, which involve data reduction, data display, and validation. Furthermore, the technique used to ensure data credibility is internal validity. The findings indicate that the educational efforts carried out by the head and members of KPPS have a positive impact on strengthening the community’s understanding of the voting process, vote tabulation, and overall election procedures. These efforts also contribute to increasing public participation in the 2024 General Election. In addition, such educational initiatives encourage the community to use their voting rights more wisely. Therefore, enhancing the educational role of KPPS can be considered an effective strategy to improve integrity and public trust in election administration at the local level.